SELEÇÃO E CARACTERIZAÇÃO MOLECULAR DE BACILLUS THURINGIENSIS BERLINER COM ATIVIDADE TÓXICA PARA TRICHOPLUSIA NI HUEBNER (LEPIDOPTERA: NOCTUIDAE) - Grecco, E.d.; Polanczyk, R.a. [UNESP]; Pratissoli, D. (Instituto Biológico, 2021)
Trichoplusia ni is a polyphagous pest that is becoming a major pest in plantations of cruciferous crops, soybeans and cotton. This study was aimed to select and molecularly characterize efficient isolates of Bacillus thuringiensis (Bt) for the control of T. ni. For the bioassays of pathogenicity, an aliquot with a 3 x 108 spores/mL suspension of Bt of each isolate was applied on the surface of the artificial diet disk, previously distributed on acrylic plates with 50 larvae, distributed in 5 repetitions. In bioassays to obtain the LC50, only isolates with 100% mortality were preselected, and tests were carried out at the concentrations 102, 5 x 102, 103, 2 x 103, 4 x 103, 6 x 103, and 8 x 103 spores/mL, and the treatments consisting of 120 larvae, distributed in 3 repetitions. A molecular characterization was performed to detect the genes cry1, cry2 and Vip for the isolates which obtained mortality over 95%. Isolates HD-1 (Standard), Bt-1043N-V, Bt-1034F, Bt-1009K, Bt-1000 and Bt-969A caused 100% mortality in the test for pathogenicity and presented an LC50 of 1.17 x 103, 1.45 x 103, 1, 46 x 103, 1.01 x 103, 9.43 x 102, 1.22 x 103, respectively. Genes cry1, cry2 and Vip were not found in the isolates tested, and other Cry toxins may have been causing the mortality of T. ni, since the isolates tested are specific for the Lepidoptera order. These isolates showed potential for the control of T. ni, being aggressive to this insect, with a potential to be used in a pest management program for this species.

Trichoplusia ni é uma praga polífaga importante em plantios de crucíferas, soja e algodão. O presente estudo objetivou selecionar e caracterizar por método molecular isolados de Bacillus thuringiensis (Bt) com potencial para atuar com agentes de controle biológico de T. ni. Para os bioensaios de patogenicidade, uma alíquota com 3 x 108 esporos/mL de suspensão de Bt de cada isolado foi aplicada na superfície do disco de dieta artificial, previamente distribuída em placas de acrílico com 50 lagartas, distribuídas em 5 repetições. Nos bioensaios para a obtenção da CL50, apenas os isolados com 100% de mortalidade foram pré-selecionados, sendo testadas as seguintes concentrações: 102, 5 x 102, 103, 2 x 103, 4 x 103, 6 x 103, 8 x 103 esporos/mL, sendo os tratamentos compostos por 120 lagartas, distribuídas em 3 repetições. Foi feita caracterização molecular para detectar os genes cry1, cry2 e Vip para os isolados que obtiveram mortalidade acima de 95%. Os isolados HD-1 (Padrão), Bt-1043N-V, Bt-1034F, Bt-1009K, Bt-1000, Bt-969A causaram 100% de mortalidade nos testes de patogenicidade e CL50 de 1,17 x 103, 1,45 x 103, 1,46 x 103, 1,01 x 103, 9,43 x 102, 1,22 x 103, respectivamente. Não foram encontrados genes cry1, cry2 e Vip nos isolados testados, podendo outras toxinas Cry estar causando a mortalidade de T. ni, visto que os isolados testados são específicos para a ordem Lepidoptera. Estes isolados mostraram potencial para o controle de T. ni, sendo virulentos a este inseto, com potencial para serem utilizados em programa de manejo desta praga.
SELECTION AND MOLECULAR CHARACTERIZATION OF BACILLUS THURINGIENSIS BERLINER WITH TOXIC ACTIVITY AGAINST TRICHOPLUSIA NI HUEBNER (LEPIDOPTERA: NOCTUIDAE)
Keywords: IPM; biological control; entomopathogen; Cry toxins; MIP; controle biológico; entomopatógeno; toxinas Cry